The delayed recovery of the remobilized rat tibialis anterior muscle reflects a defect in proliferative and terminal differentiation that impairs early regenerative processes. Issue 1 (31st March 2015) - Slimani, Lamia; Vazeille, Emilie; Deval, Christiane; Meunier, Bruno; Polge, Cécile; Dardevet, Dominique; Béchet, Daniel; Taillandier, Daniel; Micol, Didier; Listrat, Anne; Attaix, Didier; Combaret, Lydie
Abstract: Background: The immobilization‐induced tibialis anterior (TA) muscle atrophy worsens after cast removal and is associated with altered extracellular matrix (ECM) composition. The secreted protein acidic and rich in cysteine (Sparc) is an ECM component involved in Akt activation and in β‐catenin stabilization, which controls protein turnover and induces muscle regulatory factors (MRFs), respectively. We hypothesized that ECM alterations may influence these intracellular signalling pathways controlling TA muscle mass. Methods: Six‐month‐old Wistar rats were subjected to hindlimb cast immobilization for 8 days (I8) or not (I0) and allowed to recover for 1 to 10 days (R1–10). Results: The TA atrophy during remobilization correlated with reduced fibre cross‐sectional area and thickening of endomysium. mRNA levels for Sparc increased during remobilization until R10 and for integrin‐α7 and ‐β1 at I8 and R1. Integrin‐linked kinase protein levels increased during immobilization and remobilization until R10. This was inversely correlated with changes in Akt phosphorylation. β‐Catenin protein levels increased in the remobilized TA at R1 and R10. mRNA levels of the proliferative MRFs (Myf5 and MyoD) increased at I8 and R1, respectively, without changes in Myf5 protein levels. In contrast, myogenin mRNA levels (a terminal differentiation MRF) decreased at R1, but only increased at R10 in remobilized muscles, as for protein levels. Conclusions: Altogether, this suggests that the TA inefficiently attempted to preserve regeneration during immobilization by increasing transcription of proliferative MRFs, and that the TA could engage recovery during remobilization only when the terminal differentiation step of regeneration is enhanced.